Patient acceptance of HIV testing services in rural emergency departments in South Africa - Aditi Rao (Southern African Journal of HIV Medicine, 2020)
Background: South Africa faces the highest burden of HIV infection globally. The National Strategic Plan on HIV recommends provider-initiated HIV counselling and testing (HCT) in all healthcare facilities. However, HIV continues to overwhelm the healthcare system. Emergency department (ED)-based HCT could address unmet testing needs.